THE EFFECT OF FINANCIAL DISTRESS, PROFITABILITY, AND SOLVENCY ON AUDIT REPORT LAG WITH AUDIT COMMITTEE AS MODERATING VARIABLE - Putra, Mario Pratama; Nindito, Marsellisa; Khairunnisa, Hera (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the effect of financial distress, profitability, and solvency on audit report lag with an audit committee, and examine the role of the audit committee as a moderating variable. The sampling technique used a non-probability sampling method with a purposive sampling approach. The data used is secondary data sourced from the annual reports of non-primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The analysis technique used is panel regression with Moderated Regression Analysis (MRA) using Eviews 13 and Microsoft Excel software. The results showed: (a) financial distress has no effect on audit report lag; (b) profitability has no effect on audit report lag; (c) solvency has a negative effect on audit report lag; (d) audit committee has a negative effect on audit report lag; (e) the audit committee cannot moderate the effect of financial distress on audit report lag; (f) the audit committee cannot moderate the effect of profitability on audit report lag; (g) the audit committee is able to moderate the effect of solvency on audit report lag.